2013
DOI: 10.5547/01956574.34.3.7
|View full text |Cite
|
Sign up to set email alerts
|

Physical Markets, Paper Markets and the WTI-Brent Spread

Abstract: We document that, starting in the Fall of2008, the benchmark West Texas Intermediate (WTI) crude oil has periodically traded at unheard-of discounts to the corresponding Brent benchmark. We further document that this discount is not reflected in spreads between Brent and other benchmarks that are directly comparable to WTI. Drawing on extant models linking oil inventory conditions to the futures term structure, we test empirically several conjectures about how calendar and commodity spreads (nearby vs. first-d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
63
4

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 69 publications
(84 citation statements)
references
References 60 publications
11
63
4
Order By: Relevance
“…First, as Büyükşahin et al (2013) have shown structural breaks in WTI-Brent spread levels in 2008 and 2010, whereas we have found the persistence change in late 2010, how can these two statistical patterns be distinguished, and can they co-exist? Second, both WTI and Brent oil prices experienced a sharp decline in the first half of 2015 and the spreads have narrowed to the range of $5-10 per barrel.…”
Section: Discussionmentioning
confidence: 87%
See 2 more Smart Citations
“…First, as Büyükşahin et al (2013) have shown structural breaks in WTI-Brent spread levels in 2008 and 2010, whereas we have found the persistence change in late 2010, how can these two statistical patterns be distinguished, and can they co-exist? Second, both WTI and Brent oil prices experienced a sharp decline in the first half of 2015 and the spreads have narrowed to the range of $5-10 per barrel.…”
Section: Discussionmentioning
confidence: 87%
“…Lee et al (2010) also found structural breaks in the conditional variance and jump intensity of WTI crude oil prices, with an estimated breakpoint at the end of 1999. There have been very few empirical studies of structural breaks in the WTI-Brent spread dynamics; an exception being that of Büyükşahin et al (2013), which focused on the level of change. They assumed two breakpoints in the spreads, in 2008 and 2010, and then applied the Chow F-test to examine their conjecture.…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…The dramatic increase in Brent-WTI spread generated a great deal of median attention, most notably because its cause was so unclear. Many media describe this as a result of the "bottleneck" problem in Cushing, OK, which is consistent with some academic studies such as Buyuksahin et al (2013), but the actual source of shocks that induced the bottleneck problem has not been convincingly identified.…”
mentioning
confidence: 54%
“…Many commentators have attributed this price differential to a combination of factors. Infrastructural problems, coupled with expanding production, have led to a glut of crude oil at Cushing, Oklahoma, where WTI is priced (Büyükşahin et al, 2013). Excess supply of oil in the Midwest and falling oil production in the North Sea (IEA, 2014;Montepeque, 2013) have therefore decreased the WTI price relative to the price of Brent.…”
Section: Forecasts Based On Different Crude Oil Pricesmentioning
confidence: 97%